SISTEM PROTEKSI TEMPERATUR LEBIH PADA INVERTER PEMBANGKIT LISTRIK TENAGA SURYA MENGGUNAKAN ARDUINO - Febrin Aulia Batubara; Suprianto Suprianto (Jurnal Mantik Penusa)
The excess temperature in the inverter will cause a decrease in efficiency. The research of over temperature protection systems on solar power generation inverters using Arduino aims to design an over temperature protection system on PLTS inverters using Arduino so that there is no reduction in efficiency and prevents the inverter components from damage due to heating. The method used is an experimental method that is designing an over temperature protection system on the inverter to get good design results. The equipment used is solar panels, inverters, fan motors, L298N drivers, Arduino and batteries. The results showed that the over temperature protection system equipment on the PLTS inverter using Arduino was able to protect the over heating in the inverter, especially to increase the load from 272 watts to 532 watts with an increase in temperature of only 0.1 0C. For the use of an inverter for a long time, the temperature inside the inverter in the previous state greatly affects the temperature inside the inverter in the next state so that the temperature decrease along with the linear load decrease is difficult to achieve, especially at 630 watts with an inverter temperature of 37.6 0C, some time after that a decrease in load occurs until the load becomes 105 watts but the temperature value in the inverter has a value greater than the 630 watts loading that is equal to 37.9 0C